SERBIAN AGRARIAN POLICY IN THE VORTEX OF HIGH INFLATION AND GEOPOLITICAL RISKS - Aničić, Jugoslav; Vujić, Milan; Aničić, Dušan; Vojinović, Željko (Economics of Agriculture, 2023)
Attempts to solve economic crisis by a massive injection of money into the financial system have caused inflation in most highly developed countries. World economy is burdened by a high inflation, excessed demand, over indebtedness, in one word unready for the challenges that followed on the geopolitical level, and have spilled over into the economy. This situation has also affected agriculture, while the rise in food prices was particularly sensitive because it has affected the population life standard. All existing weaknesses of the economic and agrarian policy of Serbia and absence of a serious long-term strategy in this seriously in crisis sector’s development have surfaced. This paper analyses a situation in the Serbian agricultural sector, which has been pressured at the same time by bad agrarian policy, numerous internal weaknesses and big geopolitical risks.